5-year results of accelerated partial breast irradiation using sole interstitial multicatheter brachytherapy versus whole-breast irradiation with boost after breast-conserving surgery for low-risk invasive and in-situ carcinoma of the female breast: a randomised, phase 3, non-inferiority trial. Issue 10015 (16th January 2016) - Strnad, Vratislav; Ott, Oliver J; Hildebrandt, Guido; Kauer-Dorner, Daniela; Knauerhase, Hellen; Major, Tibor; Lyczek, Jaroslaw; Guinot, Jose Luis; Dunst, Jürgen; Miguelez, Cristina Gutierrez; Slampa, Pavel; Allgäuer, Michael; et al.
Summary: Background: In a phase 3, randomised, non-inferiority trial, accelerated partial breast irradiation (APBI) for patients with stage 0, I, and IIA breast cancer who underwent breast-conserving treatment was compared with whole-breast irradiation. Here, we present 5-year follow-up results. Methods: We did a phase 3, randomised, non-inferiority trial at 16 hospitals and medical centres in seven European countries. 1184 patients with low-risk invasive and ductal carcinoma in situ treated with breast-conserving surgery were centrally randomised to either whole-breast irradiation or APBI using multicatheter brachytherapy. The primary endpoint was local recurrence. Analysis was done according to treatment received. This trial is registered with ClinicalTrials.gov, number NCT00402519 . Findings: Between April 20, 2004, and July 30, 2009, 551 patients had whole-breast irradiation with tumour-bed boost and 633 patients received APBI using interstitial multicatheter brachytherapy. At 5-year follow-up, nine patients treated with APBI and five patients receiving whole-breast irradiation had a local recurrence; the cumulative incidence of local recurrence was 1·44% (95% CI 0·51–2·38) with APBI and 0·92% (0·12–1·73) with whole-breast irradiation (difference 0·52%, 95% CI −0·72 to 1·75; p=0·42). No grade 4 late side-effects were reported. The 5-year risk of grade 2–3 late side-effects to the skin was 3·2% with APBI versus 5·7% with whole-breast irradiation (p=0·08), and 5-year risk of grade 2–3 subcutaneous tissue late side-effects was 7·6% versus 6·3% (p=0·53). The risk of severe (grade 3) fibrosis at 5 years was 0·2% with whole-breast irradiation and 0% with APBI (p=0·46). Interpretation: The difference between treatments was below the relevance margin of 3 percentage points. Therefore, adjuvant APBI using multicatheter brachytherapy after breast-conserving surgery in patients with early breast cancer is not inferior to adjuvant whole-breast irradiation with respect to 5-year local control, disease-free survival, and overall survival. Funding: German Cancer Aid.